The nexus between CO2 emissions from electricity generation, GDP and energy intensity using a complete maximum entropy approach: the case of Iran - Zanjani, Zeinab (2022)
This study examines the nexus between energy intensity (EI), gross domestic product (GDP) and carbon emissions from electricity generation (CEEG) in Iran, where energy intensity has been increasing during the last decades. Iran holds one of the world’s largest fossil fuel reserves and its electricity sector is highly dependent on natural gas. In recent years, the empirical literature focuses on intensity and efficiency of energy due to global warming and climate change resulting from burning conventional fossil fuels. Therefore, finding the role and impact of energy intensity in an economy is assumed as a very important issue. The results of the current study show a positive impact of EI on CEEG, and no impact of EI on GDP. On the other hand, a nexus between CEEG and GDP is clearly identified in all the scenarios considered in the study. The generalized maximum entropy estimator is used to estimate all the parameters of the replicated models generated by the maximum entropy bootstrap for time series, which represents a novelty and an important improvement towards stability of the entire estimation procedure.